The production of English vowels by native Arabic speakers - Alqarni, Hanan, author; Delahunty, Gerald, advisor; Holland, Cory, advisor; Hirchi, Mohammed, committee member (Colorado State University. Libraries, 2018)
When Arabic learners first delve into the English language, they may find many difficulties in pronunciation due to the fact that there are vast differences between English and Arabic, especially regarding the number of vowels and their acoustic realizations. Very few studies have investigated this area of English language acquisition. The aim of this study is to examine the production of English vowels by Arabic speakers and to examine if there are gender differences in the production of English vowels by Arabic English learners. By using the phonetic software Praat, the values of duration and formant of vowel sounds was measured and obtained. English vowels produced by the subjects were recorded and analyzed using Praat, and were compared to results from a research project looking at English native speakers in Colorado. Since the participants were exposed to English and had lived in Colorado, USA, differences in vowel production were discussed and an analysis was conducted. The result of this study displayed that there are significant differences between Saudi ELLs and Colorado English native speakers in almost all the vowels. In addition, this study revealed the significant role of gender and regional dialect in producing English vowels by Arabic speakers.